Effect of Physical Exercise on Sleep Quality and Depressive Symptoms in Adults: A Systematic Review and Meta-Analysis - de Almeida, José Ricardo Vieira; Barros, Gleydson Vieira da Silva; da Silva Valente, Vitor José Monteiro Borges; Santana, Welyson Lima; dos Santos, Elton Carlos Felinto; Aguiar, José Lucas Porto; Farah, Breno Quintella; Filho, Ozeas de Lima Lins (Sleep Science, 2025)
Improvements in sleep quality and depressive symptoms are considered a cornerstone of adult health. Physical exercise is one of the interventions used to treat people with sleep disorders and improve mental health. However, there is no standardization regarding the physical exercise protocols and their effects on sleep quality and depressive symptoms in adults. The present study aims to verify, through a systematic review and meta-analysis, the effect of physical exercise on sleep quality and symptoms of depression in adults. This study adhered to the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement and was registered in the International Prospective Register of Systematic Reviews (PROSPERO). The PubMed, Cochrane Library, and Scopus databases were used to identify relevant original articles and clinical trials. Analysis was performed with Review Manager (RevMan) software (The Cochrane Collaboration, London, United Kingdom), version 5.4. The study included men and women over 18-years-old, with physical exercise as the intervention. The studies included pre- and postevaluation of sleep quality and depressive symptoms. A total of 931 articles were found, of which 15 met the eligibility criteria, encompassing 940 participants. Physical exercise significantly improved sleep quality (mean difference: -1.19; 95% confidence interval [95%CI]: −1.66 to −0.73) and depressive symptoms (mean difference: −3.51; 95%CI: −4.66 to −2.36). Aerobic exercise was the most common and effective for both outcomes. Thus, physical exercise was effective in improving sleep quality and depressive symptoms in adults. Additional studies, however, should be performed to confirm these findings.
Keywords: depression; major depression; exercise; physical exercise; sleep quality; sleep